Elaboración de un protocolo de mantenimiento preventivo para las áreas de proceso y equipos de la empresa Gecolsa CAT - David Mesa, Walter Humberto (Universidad Antonio Nariño, 2021)
In this project a proposal is developed for the realization of a preventive maintenance protocol for the repair and quality control systems of the company Gecolsa CAT, belonging to three areas that within the facilities are part of the set of tools that allow carrying carry out the equipment repair process within the company. In the first phase of the project, a detailed inspection of the electromechanical components that make up each space individually is carried out, separating each set of equipment found in the rooms mentioned. After this, it will be allowed to develop the second phase, in which CVs, protocols and maintenance schedules of each of the equipment considered will be prepared. With this project, it is expected to develop a program that, if applied, will generate an extension of the useful life of the components of each equipment, reducing setbacks during the production and repair processes. This project is developed with the endorsement of all the company's maintenance personnel, from the area manager, maintenance manager and maintenance technicians. In addition to the company, who will see a better performance in its facilities and equipment, it is they, the maintenance personnel who will directly benefit, since they will have a protocolized order, which will allow us to see better results and distribution of maintenance times, with the main objective of improving both the quality and the useful life of the equipment. It is clear to mention that during maintenance routines safety comes first, and that all necessary measures must be taken to successfully complete each of the activities carried out. Therefore, it should be reflected in each maintenance activity the different safety checklists that precede each action that is taken during the entire maintenance routine, all this, taking into account that, above all, at home, someone is waiting for us.